Cultivation and Cryopservation of Protozoan Intestinal Parasites - Kyrychenko, Igor; Biriukov, Mykhailo; Pokhil, Sergiy; Tymchenko, Olena (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):300